1983
DOI: 10.1182/blood.v61.6.1125.bloodjournal6161125
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of terminal deoxynucleotidyl transferase positive cells in the human fetus

Abstract: he ontogeny of cells containing the enzyme terminal deoxynucleotidyl transferase (TdT) in human fetal liver, bone marrow, and thymus has been studied using a highly specific antiserum to TdT together with monoclonal antiprecursor cell antibodies in double and triple marker immunofluorescence. TdT+ cells were first observed in fetal liver at 12 wk of gestation and accounted for 55% of the lymphoid-like cells isolated after Ficoll-Hypaque separation. TdT+ cells were first observed in the bone marrow 16 wk after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In addition to demonstrating time-and location-dependent appearance of CD7+ cells in human fetal tissues, our studies have directly demonstrated that CD7 + cells within fetal liver contain cells capable of CFU T formation (Table V), and that CD7 + CFUT contain cells of the T lineage (Table VII). A large number of studies have investigated the phenotype of human and murine T cell precursors from a variety of sources (16,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) . Murine and human postnatal bone marrow (BM) T cell precursors have been reported to be TdT + (47,52) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to demonstrating time-and location-dependent appearance of CD7+ cells in human fetal tissues, our studies have directly demonstrated that CD7 + cells within fetal liver contain cells capable of CFU T formation (Table V), and that CD7 + CFUT contain cells of the T lineage (Table VII). A large number of studies have investigated the phenotype of human and murine T cell precursors from a variety of sources (16,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) . Murine and human postnatal bone marrow (BM) T cell precursors have been reported to be TdT + (47,52) .…”
Section: Discussionmentioning
confidence: 99%
“…Human postnatal BM T cell precursors have been postulated to reside in the RFB-1 +, CD7 +, TdT+ population of cells (47,52) . RFB-1 +, TdT + cells in human fetal liver have also been postulated to contain T cell precursors (54,55). In postnatal human thymus, a population of CD7+, CD2 -, CD3 -, CD4-, CD8-, WT31 -cells have been identified that are germline in configuration for Tip genes and express cytoplasmic but not surface CD3 molecules (58).…”
Section: Discussionmentioning
confidence: 99%
“…8,53,54 A diverse TCR repertoire is closely linked to the required clonal complexity of the T-cell response against specific viral components. 55 Neonatal mice have diminished CTL responses to both dominant and subdominant epitopes for influenza virus 56 [58][59][60] As human fetal gestational age increases, the CDR3 length increases. 61,62 Rechavi and colleagues interrogated the total T-cell repertoire by next generation sequencing in a small number of fetal samples from selective fetal reduction cases, 12-26 weeks gestation, compared to children aged 9-48 months.…”
Section: An Important Component Of the Apc And T-cell Interaction Is Atmentioning
confidence: 99%
“…In neonatal mice, the activity of terminal deoxynucleotide transferase (TdT), the enzyme responsible for template-independent nucleotide additions, is detected around 1 week of life and this activity correlates with the acquisition of an increased diversity of CDR3 sequences ( 125 ). In humans, TdT activity is detectable in the fetal thymus from the 20th week of gestation ( 126 ). As single positive thymocytes are already detected at 14th week of gestation, the diversity of the T cell repertoire may increase during the second trimester of gestation in humans as it does during the first week after birth in the mouse and this may influence the recognition of pathogen-derived peptides ( 125 ).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%